Digital tourism communication model to increase public awareness of the Lok Baintan floating market tourist destination - Rachmawati, Dewi; Hamdani, Ayu Rakhmi Tiara; Ramonita, Latifa (Jurnal Komunikasi, 2026)
Developments in information technology and social media have transformed the way tourism destinations are recognized and promoted. Tourists' digital activities, such as uploading photos, videos, and reviews on various platforms, play a crucial role in increasing destination awareness and image. This is also true for tourism at the Lok Baintan floating market. Optimizing digital power is crucial to strengthening the floating market's presence and appeal asa unique tourist destination. This study aims to analyze the digital tourism communication model in increasing tourism awareness at the Lok Baintan Floating Market. A descriptive qualitative method with a constructivist paradigm was applied in this study. The research finding shows that integrating the AISAS (Attention, Interest, Search, Action, Share) model with the User-Generated Content (UGC) concept provides a comprehensive explanation of digital tourist behavior. Each AISAS stage is dynamic, starting with Attention and Interest, triggered by visual and narrative content from visitors and local influencers that showcase the authenticity of Banjar culture.